Optimizing The Role Of Parents In Improving Adolescents' Healthy Eating Patterns, Nutrition Education Program In Ringinsari, Blabak, Kediri Regency, Jawa Timur - Komariyah, Siti; Lia Agustin; Dian Rahmawati (Universitas STRADA Indonesia, 2025)
Adolescent nutritional problems in Indonesia are still high, often caused by unhealthy snacking habits and skipping breakfast, which reduce concentration during learning. Parents, especially mothers, play an important role in shaping adolescents’ eating patterns. This community service aimed to improve parental knowledge about balanced nutrition for adolescents. The program was conducted in Ringinsari Village, Blabak, Kediri Regency, with 25 parents of adolescents as participants. The method used was health education through lectures and discussions, supported by PowerPoint slides and leaflets. Knowledge assessment was carried out using pre-test and post-test questionnaires. The results showed a significant increase in participants’ knowledge, with the average score rising from 39.58 to 76.04. In addition, 96% of participants rated the presentation of the material as excellent, and 100% stated that the activity was beneficial. In conclusion, balanced nutrition education for parents effectively improved their knowledge and awareness, and further collaboration with schools and health workers is recommended to sustain healthy eating habits among adolescents.